2021
DOI: 10.1021/acsanm.0c02467
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Modified Electrochemiluminescent Tris(4,4’-Dicarboxylicacid-2,2’-Bipyridyl)Ruthenium(II) Dichloride and Assistant DNA-Modified Carbon Nitride Quantum Dots for Hg2+ Detection

Abstract: Accurate determination of hazardous Hg2+ is particularly essential for the environment safety and human health. In this work, using Hg2+ as a bridge for the electrochemiluminescence (ECL) reagent and the corresponding coreactant, a new type of self-enhanced ECL nanomaterial was simply and controllably prepared for the first time. In detail, tris (4,4′-dicarboxylicacid-2,2′-bipyridyl) ruthenium­(II) dichloride modified with DNA1 (Ru-DNA1) and graphite-like carbon nitride quantum dots linked with DNA2 (QDs-DNA2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Therefore, the change of ECL intensity showed a good linear relationship with Pb 2 + concentration from 5.0 × 10 À 11 to 1.0 × 10 À 6 M. Kratochvílova found that the T-Hg 2 + -T structure was highly stable and could accelerate the charge transport rate in DNA [103]. To further improve the performance, Li et al prepared a new type of self-enhanced ECL nanomaterial (Ru-DNA1-Hg 2 + -DNA2-QDs) by combining the luminophore and the co-reactant into material through the T-Hg 2 + -T structure [104]. As shown in Figure 16, the ECL signal of self-reinforcing material formed by T-Hg 2 + -T is obviously enhanced, and the ECL signal of Ru-DNA1-Hg 2 + -QDs-DNA2 could be controllably regulated by…”
Section: Ecl Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the change of ECL intensity showed a good linear relationship with Pb 2 + concentration from 5.0 × 10 À 11 to 1.0 × 10 À 6 M. Kratochvílova found that the T-Hg 2 + -T structure was highly stable and could accelerate the charge transport rate in DNA [103]. To further improve the performance, Li et al prepared a new type of self-enhanced ECL nanomaterial (Ru-DNA1-Hg 2 + -DNA2-QDs) by combining the luminophore and the co-reactant into material through the T-Hg 2 + -T structure [104]. As shown in Figure 16, the ECL signal of self-reinforcing material formed by T-Hg 2 + -T is obviously enhanced, and the ECL signal of Ru-DNA1-Hg 2 + -QDs-DNA2 could be controllably regulated by…”
Section: Ecl Systemmentioning
confidence: 99%
“…To further improve the performance, Li et al. prepared a new type of self‐enhanced ECL nanomaterial (Ru‐DNA1‐Hg 2+ ‐DNA2‐QDs) by combining the luminophore and the co‐reactant into material through the T‐Hg 2+ ‐T structure [104]. As shown in Figure 16, the ECL signal of self‐reinforcing material formed by T‐Hg 2+ ‐T is obviously enhanced, and the ECL signal of Ru‐DNA1‐Hg 2+ ‐QDs‐DNA2 could be controllably regulated by adjusting the Hg 2+ concentration.…”
Section: Application Of Carbon‐based Quantum Dots For Heavy Metal Ion...mentioning
confidence: 99%
“…As one of the most hazardous and notorious contaminants, mercury has caught particular attention of the researchers worldwide because of its high toxicity to humans and the ecosystem. Among the different states of mercury, mercuric ions (Hg 2+ ) are the most stable form, which can be dissolved in water leading to contamination of aquatic ecosystems. Mercuric ions are non-biodegradable and can be accumulated in the biological body through the food chain. Owing to the strong binding capacity of Hg 2+ for sulfhydryl groups in proteins and enzymes, excessive mercury exposure will result in several serious illnesses such as kidney damage, respiratory failure, acrodynia, nervous disorder, Hunter–Russell syndrome, and so forth. Hence, it is imperative to resolve the Hg­(II) pollution without delay.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, electrochemical techniques are also widely used in DNA probe-based mercury sensors. [21][22][23] Usually, the electrode is easily modified with nucleic acid due to its excellent biocompatibility, and the sensing of the Hg 2+ can be realized based on the target-induced formation of T-Hg 2+ -T mismatch structures on the interface. 24 Although this kind of method has satisfactory sensitivity and selectivity, for practical on-site detection applications, ensuring repeatability and stability remains a challenge.…”
Section: Introductionmentioning
confidence: 99%